Exploring the molecular landscape of multicomponent crystals formed by naproxen drug and acridines. Issue 39 (15th September 2022) - Mirocki, Artur; Lopresti, Mattia; Palin, Luca; Conterosito, Eleonora; Sikorski, Artur; Milanesio, Marco
Abstract : Three cocrystals were obtained by naproxen and acridines, optimizing the yield to more than 99% with LAG. The two structures by solution show a host-guest structure, while that by LAG a layered one, with no interconversion between parent structures. Abstract : The cocrystallization of active pharmaceutical ingredient naproxen with some acridines (acridine, 9-aminoacridine, 6, 9-diamino-2-ethoxyacridine) has been explored and the conditions under which the crystallization can be carried out have been investigated. While the crystallization of acridine-based molecular crystals was widely studied under solution conditions, solvent-free and/or mechanochemical method potentialities are still unknown. To fill this gap, the cocrystallization of naproxen with the above-mentioned acridines was attempted using different approaches, e.g., by heat treatment of the dry mechanical mixture and by liquid-assisted grinding (LAG), as alternatives to the traditional precipitation by a proper solution. In the first case, the reaction is driven under dry conditions by the temperature and gave no results independently of the temperature used, below or above the melting point of the reactants. In the second case, the reaction is driven by the mechanical action of grinding assisted by a few drops of solvent to facilitate and improve the reaction. This screening allowed obtaining three new molecular crystals for naproxen coupled to acridine and a mono-aminoacridine and solved by single-crystal and powder X-ray diffraction (PXRD). Two host–guest structures were obtained by solution crystallization, while a layered structure was obtained under LAG conditions. Interconversion between molecular crystals formed by the same chemical species was hindered once a molecular crystal was obtained by a specific technique. Hirshfeld and energy framework calculations confirmed the remarkable structural differences between 1α and 1β packing and suggested that 1β is kinetically more stable. Variable-temperature PXRD, DSC and TGA were used to explore the stability of the compounds. 6, 9-Diamino-2-ethoxyacridine proved to be too polar and/or too bulky to form crystals with naproxen regardless of the preparation method and the different stoichiometric ratios used. It is noteworthy that LAG allowed the preparation of the naproxen/acridine molecular crystal with a yield higher than 99% under almost solvent-free conditions. DSC indicated the formation of a eutectic between naproxen and acridine, with the possibility of recrystallizing the 1 : 1 complex also from the melt solution.